Avifauna de los Pueblos Santos de la Sierra Madre del Sur de Guerrero: análisis de la riqueza y recambio taxonómico entre tipos de vegetación - Sierra-Morales, Pablo; Álvarez-Álvarez, Edson A.; Almazán-Núñez, R. Carlos; Jiménez-Hernández, Javier; Méndez-Bahena, Alfredo (Instituto de Ecología, A.C., 2018)
The Sierra Madre del Sur is a region biologically important for its high levels of richness and endemism. In the last two decades, the pressure on their natural resources has increased, which threatens its biodiversity. In this study, we analyzed the bird biodiversity of the Pueblos Santos in the Sierra Madre del Sur, state of Guerrero and the species turnover was evaluated among the main vegetation types present: cloud forest, pine-oak forest, oak-pine forest, semideciduous forest and tropical dry forest. The field work was performed in 11 months distributed from 2006 to 2012. The species records were obtained through visual and auditory methods and capture of specimens.Birds were categorized by their seasonality, endemism, and risk category. A total of 136 species were recorded corresponding to 34 families and 15 orders. Cloud forest had the higher species richness (70 species), followed by oak-pine forest (59), tropical dry forest (46) and semideciduous forest (24). The greatest number of resident species (64 species) was found in the cloud forest and the highest number of migratory species (12 species) was registered in tropical dry forest. A total of 15 endemic species to Mexico and four quasi-endemic species were registered, of which the tropical dry forest had the highest number of species. Nine threatened species and nine species under special protection were registered. The cloud forest had the highest number of species at risk (16 species). There was a greater similarity in the composition of birds between the cloud forest and pine-oak forest, while the tropical dry forest presented the greatest difference in relation to the other vegetation types. In terms of the richness-area relationship, the bird biodiversity and the richness of endemism in the Pueblos Santos are high. This avifauna, as well as the vegetation types that they occupy in the region, will require of management and conservation strategies to ensure their long-term permanence.